Determinants of Stock Returns in Indonesian Property and Real Estate Firms, 2020–2024 - Ahmad Rifqi Yunus; Uhud Darmawan Natsir; Anwar; Muh. Ichwan Musa; Abdul Rahman (PT. Maju Malaqbi Makkarana, 2026)
This study aims to examine the partial influence of firm size, firm value, and systematic risk on stock returns of companies in the property and real estate sector listed on the Indonesia Stock Exchange during the 2020 –2024 period. The research employs a quantitative approach and utilizes documentation methods. The population of this study consists of all property and Real estate sector companies within the 2020 –2024 period, The sample was selected using purposive sampling based on predetermined criteria, resulting in 14 companies. Panel data regression analysis was conducted using the Economic Views (EViews) version 12 software. The findings of the study reveal that, Firm size has a positive and significant effect on stock returns of property and real estate sector companies during the 2020–2024 period. Furthermore, firm value (PBV) is shown to have a positive and significant effect on stock returns, and systematic risk (Beta) likewise exerts a positive and significant influence on stock Returns within the same period.